THE IMPLEMENTATION ANALYSIS OF SELF ASSESSMENT TO ASSESS THE STUDENT OF XI SENIOR HIGH SCHOOL PERFORMANCE IN CHEMISTRY EQUILIBRIUM PRACTICUM - Iis Intan Widiyowati; Fitria Usmanti (PROSIDING SEMINAR KIMIA, 2013)
Assessment is one of activity to measure and assess the achievement level of curriculum and success or not the process of learning, it is also used to know the strengths and weakness consisted in learning process. One of the alternative of assessment is self assessment. In this research, there is an analysis about implementation of self assessment to assess student of XI SMA performance in Chemistry Equilibrium practicum. This research used descriptive method, that describes a phenomenon in learning with statistical measures. This research instrument is compiled according to self assesment implementation rubric.This rubric consists of phases of self assessment implementation to assess student performance in practicum and contains several components such as ideal criteria of self assessment implementation, indicators of achievement, implementation stages feasibility, and data sources. The collecting data of this research comes from self assessment implementation, Student ability to do the self assessment, student performance. The collecting data in this research uses self assessment sheet.self assessment observation sheet, student questionairre, and student interview guide.All research data will be analyzed. The analysis result will be connected to literature, so it will conclude the implementation of self assessment in assess performance of practicum that has been done. This research result show that student ability on self assessment in scholl is very good. The student is categorized as very good in assess his or her performance. It indicates that the ideal criteria on implementation self assessment has been accomplished.